2018
DOI: 10.1007/s00264-018-3936-5
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for delaying surgery following hip fractures and its impact on one year mortality

Abstract: This study suggests that waiting time for hip fracture surgery more than two days was not associated with higher complication or mortality rate if waiting was to stabilize patients with active comorbidities at admission, compared to stable patients at admission with early surgery. Although early surgery within two days from admission is desirable for stable patients at admission, in patients with complex comorbidities, the surgery should be performed once they are optimized. However, the patients with delayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 29 publications
2
48
0
1
Order By: Relevance
“…AHF surgery is usually performed during daytime and as optimization seldom takes place during night, this may render that patients admitted during evening and later, may have less time for pre‐optimization. In line with this, it has been shown that AHF patients receiving active care pre‐surgery do not have increased mortality even if stipulated time limits are exceeded, whereas those whose surgery are postponed due to organizational reasons have higher mortality . Speculatively, ASA III patients, which constitute a major part (almost 50%) of our AHF patients, are perhaps the category of patients that would benefit mostly by pre‐operative optimization even if time‐to‐surgery in some cases may exceeds 24 hours …”
Section: Discussionmentioning
confidence: 71%
“…AHF surgery is usually performed during daytime and as optimization seldom takes place during night, this may render that patients admitted during evening and later, may have less time for pre‐optimization. In line with this, it has been shown that AHF patients receiving active care pre‐surgery do not have increased mortality even if stipulated time limits are exceeded, whereas those whose surgery are postponed due to organizational reasons have higher mortality . Speculatively, ASA III patients, which constitute a major part (almost 50%) of our AHF patients, are perhaps the category of patients that would benefit mostly by pre‐operative optimization even if time‐to‐surgery in some cases may exceeds 24 hours …”
Section: Discussionmentioning
confidence: 71%
“…Pollock et al did not nd male gender being a risk for readmission in 1,486 subjects after hip fracture operations [44]. Lizaur-Utrilla et al found that female gender, higher ASA score and more than 2 comorbidities are risk factors for readmission among 732 subjects after hip fractures [45]. And French et al also found that female gender and multiple comorbidities are risk factors for readmission in 41,331 subjects after hip fractures [46].…”
Section: Discussionmentioning
confidence: 99%
“…The need for COVID-19 testing procedures before being admitted to the operating room (OR) is an organizational factor that may have increased waiting times. Similarly, waiting for preoperative cardiac tests and other laboratory results may have played a role in delaying surgery [40]. A recent study describes how in Lombardy's hospitals, for instance, patients were isolated at admission and sent to a "filtering" ward until the result of nasopharyngeal swabs became available, with a mean response delay, at that time, of 12 to 24 hours [43].…”
Section: Discussionmentioning
confidence: 99%